2017
DOI: 10.1007/978-981-10-4567-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Roles of ER-Endolysosomal Contact Sites in Disease

William Mike Henne

Abstract: Inter-organelle membrane contact sites (MCSs) serve as unique microenvironments for the sensing and exchange of cellular metabolites and lipids. Though poorly defined, ER-endolysosomal contact sites are quickly becoming recognized as centers for inter-organelle lipid exchange and metabolic decision-making. Here, we review the discovery and current state of knowledge of ER-endolysosomal MCSs with particular focus on the molecular players that establish and/or utilize these contact sites in metabolism. We also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…ER-dependent Ca 2+ mobilization, in turn, could stimulate NAADP-induced Ca 2+ release through either local NAADP production or TPC sensitization by cytosolic/intraluminal Ca 2+ (please, note that only TPC1 is sensitive to intraluminal Ca 2+ ) [18]. Ultrastructural analysis revealed that the EL system can be closely (<30 nm) apposed to the ER network [163,164]. As reviewed elsewhere, endosomes-ER MCSs control lipid exchange, cargo sorting, endosome positioning, trafficking and fission [164,165].…”
Section: The Endolysosomal Ca2+ Store: Functions and Mechanisms Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…ER-dependent Ca 2+ mobilization, in turn, could stimulate NAADP-induced Ca 2+ release through either local NAADP production or TPC sensitization by cytosolic/intraluminal Ca 2+ (please, note that only TPC1 is sensitive to intraluminal Ca 2+ ) [18]. Ultrastructural analysis revealed that the EL system can be closely (<30 nm) apposed to the ER network [163,164]. As reviewed elsewhere, endosomes-ER MCSs control lipid exchange, cargo sorting, endosome positioning, trafficking and fission [164,165].…”
Section: The Endolysosomal Ca2+ Store: Functions and Mechanisms Ofmentioning
confidence: 99%
“…Ultrastructural analysis revealed that the EL system can be closely (<30 nm) apposed to the ER network [163,164]. As reviewed elsewhere, endosomes-ER MCSs control lipid exchange, cargo sorting, endosome positioning, trafficking and fission [164,165]. Notably, TPC1 favors the formation of these junctional microdomains, thereby promoting the internalization of EGF receptors and curtailing EGF signalling [149,166].…”
Section: The Endolysosomal Ca2+ Store: Functions and Mechanisms Ofmentioning
confidence: 99%
“…The general importance of ER-endolysosome contacts in HSP is more broadly supported by the recent characterization of 3 additional SPG genes that include spastin (SPG4, a microtubule severing protein), strumpellin (SPG8, involved in recycling of proteins from endosomes) and REEP1 (SPG31, a protein that shapes ER tubules) to have roles at contacts between late endsosomes and the ER (3). In addition to promoting transport of late endosomes and lysosomes, such sites might also serve as sites of lipid transfer to and from the ER (6). Consistent with the importance of such functions, lysosomal lipid accumulation occurs in SPG11 mutant mice (55).…”
Section: Insights Into Neuronal Lysosomes From Human Geneticsmentioning
confidence: 89%
“…Thus, lysosomes do not function in isolation from other organelles but require ongoing delivery of both cargos and hydrolases from the endocytic and autophagic pathways. Lysosomes additionally make contacts with other organelles including the endoplasmic reticulum (ER) (3) and potentially mitochondria (4) that are thought to allow the non-vesicular transfer of lipids and calcium (5,6).…”
mentioning
confidence: 99%
“…Interestingly, by the use of a newly developed high-resolution imaging technology Sac1, which has been shown to shuttle between ER and Golgi in response to different stimuli (Blagoveshchenskaya and Mayinger, 2009), has been recently found to reside at the ER-Trans Golgi Network (TGN) contacts sites, where its phosphatase activity controls either ER or Golgi PtdIns4P membrane content (Venditti et al, 2019a,b). ER can establish membrane contacts with TGN as well as with endosomal membranes, referred to as ER-endo-lysosomal contact sites (EELCS) (Eden, 2016; Henne, 2017).…”
Section: Discussionmentioning
confidence: 99%